Correction to: CART cells are prone to Fas- and DR5-mediated cell death. Issue 1 (25th September 2018) - Tschumi, Benjamin O.; Dumauthioz, Nina; Marti, Bastien; Zhang, Lianjun; Lanitis, Evripidis; Irving, Melita; Schneider, Pascal; Mach, Jean-Pierre; Coukos, George; Romero, Pedro; Donda, Alena
Abstract : After publication of this article [1], it was noticed that 3 authors were missed from the author list.